Language learning among higher education students: an analysis on motivation - María Luisa Rodríguez Muñoz; Jesús Claudio Pérez Gálvez; Kris Buyse (Research in Education and Learning Innovation Archives)
Intrinsic motivation in language learning is ideal to attain successful foreign language learning according to experts (Del-Castillo, 2010; Gilakjani, Leong, & Sabouri, 2012). In order to measure its impact at university level, this paper shows the results of a quantitative study conducted at KU Leuven during the academic year 2021-2022 on motivation in foreign language learning. A total of 479 students participated in a survey designed for this purpose. The methodology was based on a multivariate analysis using the statistical package SPSS v. 25. The research findings show that university students have essentially instrumental motivation for learning foreign languages (FL), which implies that their desire to acquire a second language (L2) is limited to practical purposes. On the other hand, the study has identified a representative segment of students, referred to as “in- cidental students”, who are characterised by not having any clear motivation (neither instrumental nor integrative) for FL. The results lead to recommendations for curricular adaptation to enhance intrinsic motivation in foreign language teaching and learning at university level.